PERENCANAAN KEBUTUHAN DAN PENJADWALAN BIAYA SUMBER DAYA PADA PELAKSANAAN PROYEK KONSTRUKSI - I Ketut Nudja S. (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2017)
ABSTRACT The proposed bid price should be an estimate of real cost or direct cost plus indirect cost plus profit. As is known one of the parameters that affect the value of direct costs is labor costs. In the field of labor unit prices often fluctuate, so it will affect in determining labor costs. The final outcome of this plan will be used as a basis in the labor cost control during the implementation of the project. Based on the discussion, the total cost of human resources is IDR 328.369.050,00, of labor cost IDR 183.750.000,00, foreman fee IDR 25.107.550,00, the cost of weaving IDR 47.880.000,00, the cost of a smith IDR 9,000,000.00, the cost of masonry IDR 41.350.000,00, carpentry costs IDR 1.750.000,00, smith cost IDR 183.512.000,00, the cost of masonry IDR 189.000,00, carpentry fee IDR 1.900.500,00. Keyword: planning, labor costs, construction projects